AN ASSESSMENT OF TRANSPORT LOGISTICS STUDENTS’ PERSONAL FINANCE AND THEIR PERSONAL FINANCE MANAGEMENT SKILLS - Ginavičienė, Jurgita; Sprogytė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Knowledge about personal finance, economics’ expression understanding, ability to manage own money are important nowadays. The main aim of this research is to compare the Transport Logistics students’ personal finance management skills during the Covid-19 pandemic. The respondents were 197 Transport Logistics students of Vilnius College of Technologies and Design. They filled out an electronic demographic data form online and evaluated their personal financial management skills. Results of the research showed students earnings are to 440 EUR per month. Their amount per month was more than 440 EUR, the main groups of expenses, revealed skills of saving, view into the personal control of finance and sufficient rating of knowledge.